Single-cell RNA sequence presents atlas analysis for chondrocytes in the talus and reveals the potential mechanism in coping with mechanical stress - Wang, Tianrui; Wang, Junjie; Sun, Zewen; Zhang, Lu; Yu, Chenghao; Zhao, Haibo; Yan, Mingyue; Sun, Shenjie; Ye, Zhenhao; Zhang, Yingze; Yu, Tengbo (Frontiers in Cell and Developmental Biology, 2022)
Chondrocytes are indispensable for the function of cartilage because they provide the extracellular matrix. Therefore, gaining insight into the chondrocytes may be helpful in understanding cartilage function and pinpointing potential therapeutical targets for diseases. The talus is a part of the ankle joint, which serves as the major large joint that bears body weight. Compared with the distal tibial and fibula, the talus bears much more mechanical loading, which is a risk factor for osteoarthritis (OA). However, in most individuals, OA seems to be absent in the ankle, and the cartilage of the talus seems to function normally. This study applied single-cell RNA sequencing to demonstrate atlas for chondrocyte subsets in healthy talus cartilage obtained from five volunteers, and chondrocyte subsets were annotated. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses for each cell type, cell–cell interactions, and single-cell regulatory network inference and clustering for each cell type were conducted, and hub genes for each cell type were identified. Immunohistochemical staining was used to confirm the presence and distribution of each cell type. Two new chondrocyte subsets were annotated as MirCs and SpCs. The identified and speculated novel microenvironment may pose different directions in chondrocyte composition, development, and metabolism in the talus.